Potential growth in Turkey: Sources and trends - Orhun Sevinç; Ufuk Demiroğlu; Emre Çakır; Emine Meltem Baştan (Central Bank Review (CBR), 2022)
This paper estimates potential growth in Turkey using a production function estimation approach. Our approach aims to measure the inputs of production in the most detailed fashion that is possible and empirically addresses concepts of sustainable potential growth for Turkey. While developing measures of the sources of potential growth, we provide a thorough discussion of the estimated trends in labor force participation, capital growth by asset type, and total factor productivity since the mid-2000s. Our results suggest that the key driver of potential growth has increasingly been capital accumulation. The declining trend in the positive TFP growth stands out as the key area of improvement for potential growth.
Keywords: 330; Potential GDP; Output Gap; Turkish Economy